A systematic review and narrative synthesis of prevalence rates, risk and protective factors for suicidal behavior in international students - Veresova, Maria; Lamblin, Michelle; Robinson, Jo; McKay, Samuel (Frontiers in Psychiatry, 2024)
International students are a crucial group for suicide prevention efforts. However, no comprehensive review of the prevalence, risk or protective factors for international student suicide has been conducted, complicating prevention efforts. The current systematic review addresses this issue by identifying the prevalence, risk, and protective factors for suicidal thoughts and behaviour in international students enrolled in tertiary institutions. We searched CINAHL, EMBASE, ERIC, Medline, and PsycInfo from inception to November 2023, and 24 papers met the study inclusion criteria. Eighteen studies reported on the prevalence or intensity of suicidal ideation, six reported on the prevalence of suicide attempts, and seven on the prevalence of self-harm. No studies provided data on completed suicides. Studies indicated that international students experienced similar or lower levels of suicidal ideation and self-harm, but more frequent suicide attempts than domestic students. A narrative synthesis of risk and protective factors yielded mixed results, although social isolation, comorbid mental health conditions, and experiences of racism or discrimination were commonly linked to suicidal thoughts and behaviours. The mixed evidence quality, numerous measurement issues, and low number of studies in the literature point to a need for further research on suicide among international students.